Dispensing drugs: knowledge of patients/caregivers and profile of responsible for the service (Research, Society and Development, 2022)
Introduction: Dispensing is a private act of the pharmacist to guide and provide medications to the patient or caregiver, under compensation or not, in order to ensure the proper and safe use of medication, its benefits, conservation and disposal. The act of dispensing empowers the person on the correct use of their medication, improving health and saving resources. However, users of community pharmacies do not seem to be properly oriented about what they use. Thus, the aim of this study was to assess patients' knowledge/care about their medications and the profile of the professional who provided them. Method: Cross-sectional study carried out in basic pharmacies in a municipality in Minas Gerais. After removing the medication, patients/caregivers answered a questionnaire. The information obtained was compared with the medical prescription and the package leaflet. Dispensation officials were also interviewed. The variables were analyzed using the Fisher and chi-square tests. The study was approved by the Research Ethics Committee of UNIFAL-MG. Results: From a total of 420 research participants, 81.4% patients/caregivers had knowledge about the indication and posology of the acquired medication. Of these, only 14% had knowledge about care and precautions, 6.4% understood the adverse effects, 6.7% understood drug interactions, and 39.5% knew about storage techniques. The 9 basic pharmacies used in the study did not have a pharmacist providing care. Conclusion: Most of the interviewed patients/caregivers know the purpose and posology of the medication purchased from the basic pharmacy. However, information provided in the practice of dispensing, such as care and precautions for use, interactions, adverse effects, contraindications and storage conditions are little dominated by the research participants. This fact can compromise the pharmacotherapy and, consequently, not ensure the rational use of medicines. This may also be associated with the lack of a pharmaceutical professional in dispensing and lack of training of the technical support staff.